PENGEMBANGAN LKPD BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS IV SD - WulanSari, Amanda; Budiharti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of a Student Worksheet (LKPD) based on Contextual Teaching and Learning (CTL) was motivated by the low mathematical communication skills of fourth-grade elementary school students in the topic of plane figures. Learning activities that remain teacher-centered, the lack of varied teaching methods, and limited learning media have made it difficult for students to relate mathematical concepts to real life situations. The purpose of this study was to develop a CTL-based LKPD that is valid, practical, and effective in improving the mathematical communication skills of fourth-grade elementary school students.This research employed the Research and Development (R&D) method using the 4D model (Define, Design, Develop, and Disseminate) proposed by Thiagarajan. The research subjects included material experts, media experts, classroom teachers, and fourth-grade students of SD Negeri 2 Glagah. Data collection techniques involved observation, interviews, expert validation, teacher and student response questionnaires, and learning achievement tests through pretest and posttest. Data were analyzed descriptively both qualitatively and quantitatively with the help of SPSS using the Paired Sample t-Test and N-Gain Score calculation.The results showed that the CTL-based LKPD obtained a material expert validation score of 86.6% and a media expert validation score of 86%, both categorized as very feasible. The student response reached 86.5% and the teacher response 95%, indicating that the LKPD was highly practical. The effectiveness test showed a significant improvement (Sig. 2-tailed = 0.089 < 0.05), which means there was a significant difference in students’ learning outcomes. The average N-Gain Score of 0.69 was categorized as high. Therefore, the CTL-based LKPD was declared valid, practical, and effective in improving fourth-grade students’ mathematical communication skills.